1987
DOI: 10.1161/01.cir.75.2.443
|View full text |Cite
|
Sign up to set email alerts
|

The role of endogenous opioids in congestive heart failure: effects of nalmefene on systemic and regional hemodynamics in dogs.

Abstract: We studied the role of endogenous opiates and their interrelationships with the sympathetic nervous system in an experimental preparation of right-sided congestive heart failure (CHF) produced by surgical tricuspid avulsion and progressive pulmonary arterial constriction. Three groups of dogs with CHF and one group of sham-operated dogs were studied. One group of dogs with CHF was given normal saline as pretreatment, while the other two groups were pretreated with either propranolol alone ((3-blockade) or prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…Similar chamber-specific changes have been reported in patients with right ventricular failure secondary to primary pulmonary hypertension (18). The RHF dogs have been extensively studied; they exhibit an increase in plasma catecholamines, a decrease in myocardial NE stores, a reduced responsiveness to beta-receptor agonists (19), and other neurohormonal and reflex changes (30)(31)(32)(33)(34) that occur in patients with congestive heart failure. Specific 3H uptake activity, defined as the difference in radioactivity between tissue slices incubated in a [3H]NE-containing solution at 370C (total 3H uptake) and those at 40C (nonspecific 3H uptake), was taken to approximate NE uptake activity in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Similar chamber-specific changes have been reported in patients with right ventricular failure secondary to primary pulmonary hypertension (18). The RHF dogs have been extensively studied; they exhibit an increase in plasma catecholamines, a decrease in myocardial NE stores, a reduced responsiveness to beta-receptor agonists (19), and other neurohormonal and reflex changes (30)(31)(32)(33)(34) that occur in patients with congestive heart failure. Specific 3H uptake activity, defined as the difference in radioactivity between tissue slices incubated in a [3H]NE-containing solution at 370C (total 3H uptake) and those at 40C (nonspecific 3H uptake), was taken to approximate NE uptake activity in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…[2][3][4] There is substantial evidence that cardiac opioid receptors are activated during myocardial ischemia and reperfusion, supporting the hypothesis that EOP are involved in the pathophysiology of ischemic heart disease. 12) We have shown that in patients with acute myocardial infarction, there was an increased plasma concentration of β-endorphin.…”
Section: )mentioning
confidence: 86%
“…Since the identification of EOP and opioid receptors in the heart, 1) it has become clear that EOP subserve important roles in cardiovascular regulation and are especially involved in various cardiovascular stress situations such as shock, 2) heart failure, 3) and myocardial ischemia. 4) In humans, it has been shown that opioid receptors are present in the heart and that they play an important role in myocardial ischemia.…”
mentioning
confidence: 99%
“…The precise role of ~-endorphin is not clear. However, some studies postulate that ~-endorphin may play a role in thermoregulation [37], respiratory regulation [38], hemodynamic regulation [39], and so on. In any case, a 2-week administration of nifedipine-SR had no effect on ~-endorphin.…”
Section: Discussionmentioning
confidence: 99%